PENGARUH LIKUIDITAS, LEVERAGE, AKTIVITAS, DAN PROFITABILITAS TERHADAP RETURN SAHAM (Studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia) (Students' Journal of Economic and Management, 2013)
Dinamic economics condition and always experience change from time kewaktu, in umu will influence operational a will company, in industrial group. one of [the] industrial enough sensitive towards this economics condition change manufacturing industrial. ig. k. a. ulupui (2009) analyze liquidity ratio influence, laverage, activity and profitability towards return share (study in company food and drink with consumption goods industrial category). watchfulness result demoes that variable cr, der, tat partially doesn't has influence significant towards return share. while roa has which are positive influence significant towards return share companies. while watchfulness that done by rahfiani khairurizka, et. al. (2009) with title the effect of financial ratios, firm size, and cash flow from operating activities in the interim report to the stock return show result that roe, npm, der, pbv positive influential towards return share, while CR, TATO, ta, CFO negative influential towards return share. aim from this watchfulness tests liquidity influence, leverage, activity, and profitability towards return manufacturing business share at indonesia effect exchange. Aim from this watchfulness tests liquidity influence, leverage, activity, and profitability towards return manufacturing business share at indonesia effect exchange.This watchfulness population manufacturing business mobile the share is dealed during 2006 up to 2010. watchfulness sample election technique is done according to purposive sampling so that got sample total 75 emiten. data analysis that used to answer watchfulness hypothesis is use doubled regression analyzer.This watchfulness result shows that current ratio, and debt to equity negative influential and significant towards return share, while total asset turnover, return on asset not influential significant towards return share.Keyword: Current Ratio, Total Asset Turnover, Return On Asset Debt Equity Ratio, And Return Share